2014
DOI: 10.1093/gbe/evu055
|View full text |Cite
|
Sign up to set email alerts
|

Obligate Insect Endosymbionts Exhibit Increased Ortholog Length Variation and Loss of Large Accessory Proteins Concurrent with Genome Shrinkage

Abstract: Extreme genome reduction has been observed in obligate intracellular insect mutualists and is an assumed consequence of fixed, long-term host isolation. Rapid accumulation of mutations and pseudogenization of genes no longer vital for an intracellular lifestyle, followed by deletion of many genes, are factors that lead to genome reduction. Size reductions in individual genes due to small-scale deletions have also been implicated in contributing to overall genome shrinkage. Conserved protein functional domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Another trait observed that is associated with a host-restricted lifestyle is the reduction in the maximal protein length in comparison to free-living relatives, such as P. ananatis and E. coli ( table 1 ). Some proteins involved in toxin production, secondary metabolic processes, virulence, extracellular sensing, or are of unknown function were shown to be, on average, larger than those involved in primary metabolic processes such as DNA replication, transcription, translation and essential amino acid biosynthesis, and the former, being nonessential for long-standing host-restricted lifestyles, are largely missing from insect endosymbiont genomes and their absence likely contributes to the reduced genome sizes ( Kenyon and Sabree 2014 ). Pantoea carbekii exhibits a somewhat similar genic profile in that the longest protein encoded by its genome is the 1,413 amino acids long beta′ subunit of RNA polymerase (RpoC), which is important for transcription, and it is one-third that of the longest protein encoded in the genome of a free-living relative, P. ananatis AJ13355 (putative secondary metabolite biosynthesis protein YP_005934773: 4,385 amino acids) that is of unknown function.…”
Section: Resultsmentioning
confidence: 99%
“…Another trait observed that is associated with a host-restricted lifestyle is the reduction in the maximal protein length in comparison to free-living relatives, such as P. ananatis and E. coli ( table 1 ). Some proteins involved in toxin production, secondary metabolic processes, virulence, extracellular sensing, or are of unknown function were shown to be, on average, larger than those involved in primary metabolic processes such as DNA replication, transcription, translation and essential amino acid biosynthesis, and the former, being nonessential for long-standing host-restricted lifestyles, are largely missing from insect endosymbiont genomes and their absence likely contributes to the reduced genome sizes ( Kenyon and Sabree 2014 ). Pantoea carbekii exhibits a somewhat similar genic profile in that the longest protein encoded by its genome is the 1,413 amino acids long beta′ subunit of RNA polymerase (RpoC), which is important for transcription, and it is one-third that of the longest protein encoded in the genome of a free-living relative, P. ananatis AJ13355 (putative secondary metabolite biosynthesis protein YP_005934773: 4,385 amino acids) that is of unknown function.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the genes that are lost encode functions that have been inferred to be tangential to the mutualism ( Moran et al. 2008 ; Kenyon and Sabree 2014 ; Wernegreen 2015 ). Genome reduction in insect endosymbionts has been largely characterized in hemipterans (i.e., Auchenorrhyncha and Sternorrhyncha) with strictly intracellular bacterial mutualists that are vertically transmitted within host tissues (intraegg to bacteriome), yet studies focusing on symbionts that are extracellularly and vertically transmitted, as observed in stink bugs (Pentatomomorpha; Heteroptera), are conspicuously lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular residence under stable environmental conditions results in relaxed purifying selection that subsequently facilitates mutation fixation and accumulation. Additionally, the loss of DNA repair and recombination mechanisms (as evidenced by a survey of complete genomes), erroneous DNA replication and successive genetic bottlenecks with each generation also contribute to dramatic losses of genes nonessential for the maintenance of the mutualism (Kenyon and Sabree, 2014). The abundance of genomes for endosymbionts of insect for which life history information is available, clear habitat conditions (e.g., consistent intracellular localization) and host demands (e.g., phytophagy and low assimilable nitrogen) are strongly correlated with endosymbiont gene content (e.g., maintenance of essential amino acid biosynthesis pathways).…”
Section: Genome Reductionmentioning
confidence: 99%
“…Extreme genome reduction (genomes smaller than <0.25 Mb) has only been observed in obligate intracellular symbionts (McCutcheon and Moran, 2011;Moran and Bennett, 2014), yet moderately reduced genomes (0.7-1.2 Mb) are observed in their extracellular counterparts when compared to free-living relatives, namely Pantoea ananatis and E. coli (Table 1; Kenyon et al, 2015). Additional characteristics stinkbug symbionts share with intracellular symbionts are A+T%-bias (with symbiont genomes between 69 and 75%, excluding P. stali's symbiont) and high rates of sequence evolution (Hosokawa et al, 2013;Kenyon and Sabree, 2014;Moran and Bennett, 2014). While some intracellular symbionts have lost genes involved in canonical ATP synthesis, the available extracellular symbiont genomes have retained them.…”
Section: Genome Reductionmentioning
confidence: 99%
See 1 more Smart Citation